(untitled) (Biological Sciences - PJSIR, 2005)
Intraspecific hybridization studies were carried out in two strains of Clarias gariepinus with acute and mild cephalic-abnormality or cracked-skull disease and non-cephalic or normal species from Ibadan, Oyo State, Southwestern Nigeria, and the Maiduguri strain from Maiduguri, Borno State, Northern Nigeria. The highest percentage of hatchability (84.5%) was recorded in the Maiduguri strain of C. gariepinus and the least (67.5%) in the strain with mild cephalic- abnormality. Among the intraspecific hybrids, the highest percentage (76.7%) was recorded in the cross between the female of Maiduguri strain and the male of non-cephalic strain, while the least (72.2%) was recorded in the cross involving the female of Maiduguri strain and the male of strain with cephalic-abnormality. The maximum growth recorded was 4.321g in six weeks in the strain with mild cephalic-abnormality and minimum 3.758 g in the Maiduguri strain. Among the hybrids, maximum growth of 4.086 g was recorded in the cross between the female of Maiduguri strain and the male of non-cephalic, and minimum of 3.582 g in the cross between the female with cephalic-abnormality and the male of Maiduguri strain. There was no occurrence of cephalic-abnormality in the cross between the female of C. gariepinus with cephalic-abnormality and the male of Maiduguri strain.